Influence of flow on migratory behaviour of salmon smolts - Kiviloog, Jaan; Bergdahl, Lars; Rivinoja, Peter; Lundquist, Hans (2003)
A study on the effect of flow velocity on the downstream migration of smolts, i.e. juvenile salmon and trout, in a major northern Swedish river, Ume älv, is presented. Few studies have been done on Swedish smolt migratory behaviour. This study comprises telemetric studies of downstream migrating smolts and flow velocity measurements in field. To achieve more comprehensive information about the flow field numerical simulations are carried out. This is done by solving the three dimensional Reynolds-averaged Navier-Stokes equations using the Fluent computational fluid dynamics (CFD) package. The field measurements are also used to validate the numerical flow simulation. The river Ume älv, where the study is preformed, is fully used for power production. However, its largest tributary river, Vindelälven, is unregulated and holds important spawning grounds for salmon (Salmo salar) and trout (Salmo trutta), and downstream of the confluence of the two rivers there is only one hydropower plant, the Stornorrfors power plant. This constitutes a major hindrance for fish migrating between the Bothnian Sea and the spawning grounds of the river Vindelälven. The juvenile fish leaving the Vindelälven downstream towards the ocean can migrate either through the turbines and deep rock tunnels of the power plant or through the surface weirs at the regulating dam. Because of the flow regime during the migration period of smolts most smolts are believed to follow the main stream through the turbines leading to a mortality of approximately 25 %.The objective of the study is to determine the migration paths of salmon and trout smolts and relate their behaviour to hydraulic factors. The results from the study can be used to improve smolt survival by taking appropriate measures to divert the smolts from the turbines, e.g. by changing spill rules or installing diversion systems.In spring 2002 22 salmon and 22 trout smolts were tagged with internal, individually coded radio transmitters (ATS). After the release approximately five ...